Analysis of Online Learning Readiness Level at Universitas Nahdlatul Ulama Surabaya (UNUSA) - Endang Sulistiyani; Rizqi Putri Nourma Budiarti; Muhammad Aidir Rafly (School of Industrial and System Engineering, Telkom University, 2021)
Since a few years ago, blended learning has been implemented by UNUSA. However, until now, theimplementation is still not optimal. Various obstacles, such as network access, availability ofdevices, and unclear rules in implementing online learning, still occur. Readiness analysis is one ofthe critical success in online learning implementation. The main objective of this research is toconduct online learning readiness studies at UNUSA. This research was carried out in three mainstages: the preparation of measurement instruments, data collection, and analysis of readiness level.The method used is descriptive research method with quantitative and qualitative approaches. TheSeakow & Samson e-learning readiness model with five dimensions of readiness, namely policy,technology, financial, human resource, and infrastructure, is used in this study. The result of thisstudy shows that that UNUSA's level of readiness in implementing online learning is in the Readycategory, requiring improvement to implement it with a readiness score of 3.68. The dimension withthe highest score is technology, which is 3.84. Meanwhile, infrastructure and policy scored 3.77 and3.72, respectively. The human resources dimension has a readiness score of 3.6. In contrast, thedimension with the lowest score is the financial dimension.